PROSPECTIVE LEADERS' VIEW ON ROMANIAN SOCIETAL CULTURE - CATANA GHEORGHE ALEXANDRU; CATANA DOINA (Annals of the University of Oradea: Economic Science, 2010)
This study deals with Romanian prospective leaders’ perceptions and expectations concerning the societal culture. It is a part of a European research project, GLOBE Students, dealing with the interrelations between societal culture and leadership. The basic theoretical constructs and methodological framework of investigation are those developed by GLOBE international research project. In adapting our research to student population peculiarities, GLOBE Beta questionnaire was altered through adding new items (scales). The sample consists in 429 students in business/economics and engineering, belonging to three Romanian universities. The findings show that in student’s opinion there are significant differences between societal culture practices and values (expectations) on all nine cultural dimensions in GLOBE model.